GIS-based landslide hazard mapping in Jhimruk River basin, west Nepal - Pathak, D; Gajurel, AP; Shrestha, GB (Journal of Nepal Geological Society, 2008)
The West Rapti River is one of the major rivers in west Nepal that is having two main tributaries namely the Madi River and Jhimruk River. Out of around 4,500 km2 area of the Rapti Basin, the Jhimruk Basin accounts around 960 km2. The Jhimruk River Basin mainly covers the Pyuthan District. The altitude of the basin reaches as high as 3,200 m. The catchment area of the basin is quite diverse in nature because of considerable difference in geology, altitude, climatic, biological and land use conditions. The study area primarily lies in the Sub-Himalaya (Siwaliks) in the south and Lesser Himalaya zone in the north. These two zones are separated with each other by the Main Boundary Thrust (MBT). The Siwalik rocks are basically consisting of sedimentary rocks (mudstone, sandstone, and conglomerate), while the Lesser Himalayan rocks are basically the low grade metamorphic rocks (e.g., slate, phyllite, schists, garnet-schists, metasandstone and quartzite). Generally, the range exhibits very rugged terrain with deeply dissected gullies and steep slopes. Water induced hazards, basically landslide, debris flow and flood hazards are frequently reported from the area. Landslide hazard is typically depicted on maps, which show spatial distribution of hazard classes, or “landslide hazard zonations”. The development of these zonations requires knowledge of the processes active in the area being analyzed, and factors (geological and triggering) leading to the occurrence of landslides. Landslide and debris flow hazard assessment in the Jhimruk River Basin was carried out based on the primary data collected from the field as well as the information extracted from the aerial photographs and satellite images. All these information were integrated in the GIS database, which were used to prepare several thematic layers like DEM, slope map, aspect map, land use map, drainage density map, geological and geomorphical map, landslide and debris distribution map. These were further analysed and processed in GIS environment in order to generate landslide and debris flow hazard maps. There are various methods to carry out the GIS based hazard zonation. Knowledge based approach, information value method, and fuzzy methods are some of the widely used method in landslide hazard zonation using GIS. Each method has both the superiority and drawback. In the present study, the knowledge based approach has been utilized. The result of the analysis is the generation of landslide and debris flow hazard zones. The generated hazard model was validated with the help of the observed landslides landslide/debris flow areas and a good agreement between the observed and predicted slide/flow zones was obtained. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.25